Analisis Pemahaman Konsep Matematika Siswa Kelas VII SMPS Amal Mulia 2 Cileungsi Pada Materi Operasi Hitung Bilangan Bulat : An Analysis of Seventh-Grade Students' Mathematical Concept Understanding at SMPS Amal Mulia 2 Cileungsi on Integer Arithmetic Operations - Rahmantika, Laila Eka (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the mathematical concept understanding of seventh-grade students at SMPS Amal Mulia 2 Cileungsi on the topic of integer arithmetic operations. The method used is descriptive qualitative, with data collection techniques including observation, written tests, and interviews. The results indicate that the majority of students face difficulties in understanding basic concepts, particularly regarding the operation of positive and negative signs and problem-solving strategies. This difficulty is reflected in the students' low ability to re-explain concepts and solve problems that require inter-conceptual connections. Factors causing this low concept understanding include a lack of active student engagement, conventional teaching methods, and the minimal use of contextual learning media. Therefore, a more innovative and interactive learning approach is needed to improve students' mathematical concept understanding comprehensively.